Analysis and evaluation of the economic effect of coal use for Ferroalloy and sinter production - Akhmetzhanov, B.; Tazhibekova, K.B.; Shametova А.А. (BUKETOV BUSINESS REVIEW, 2019)
The article is devoted to the search for new ways of using cheaper raw materials, as the reduction of energy costs in Ferroalloy and sinter production becomes a priority. Due to the insufficiency of the study of the features of the use of alternative fuels in metallurgy, the paper considers the theoretical background of the possibility of using coal, aimed at achieving optimal consumption of raw materials, electricity and reducing the cost of production, the analysis and evaluation of the economic efficiency of their use in Ferroalloy production and sintering. The paper presents the results of the study of the possibility of using brown coal in Kazakhstan for the metallization of iron ore and iron-containing waste. To address issues of efficiency of use of medium and high-ash coal in Ferroalloy production and agricultural production were investigated, the known methods of sintering of sinter charge, the estimation and analysis of world and domestic market of ferroalloys and agglomerates, calculation of imputed costs in the Ferroalloy and agroproizvodstve, the economic efficiency subconsumers coal in the production of ferroalloys and agglomerates. The economic efficiency of the transition to the use of low-coking coal in the production of ferroalloys is justified, which allows to reduce the cost by 23 %, reduce the price by 11 % and increase the efficiency by 10.6 %. For sinter production, respectively-cost reduction by 7 %, price reduction by 5.5 % and efficiency increase by 10.8 %.